High-insulation and high-heat-insulation composite sheet used between lithium battery cells and preparation process of high-insulation and high-heat-insulation composite sheet

By designing high-insulation and high-insulation composite sheets between lithium battery cells, combining aerogels and specific materials, the problem of insufficient insulation performance of lithium battery modules is solved, the thermal runaway protection performance and lightweight advantages are improved, and the advantages of enhanced The safety and endurance of new energy vehicles.

CN119242043APending Publication Date: 2025-01-03浙江荣泰电工器材股份有限公司
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411300888.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The thermal conductivity of the thermal insulation buffer material between the existing lithium battery cells in the lithium battery module is low, which cannot meet the needs of lightweight and thermal runaway protection performance of the power battery module.

Method used

Using high-insulating and high-thermal insulation composite sheet, by forming through holes between the lithium battery cells and filling aerogel, combined with the structural design of the base plate, cover plate and partition plate, aramid nanofibers and ultrafine mica powder are used, Materials such as nanosilicon dioxide and hollow glass microbeads have been prepared to produce composite sheets with good flame retardant, insulating and thermal insulation properties.

Benefits of technology

It improves the thermal runaway protection performance of the power battery module, enhances the driving safety performance of new energy vehicles, reduces the overall quality and extends the battery life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119242043A_ABST
    Figure CN119242043A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium battery module thermal runaway protection materials, in particular to a high-insulation and high-heat-insulation composite sheet used between lithium battery cells and a preparation process of the high-insulation and high-heat-insulation composite sheet. Through holes with heat insulation and noise reduction effects are formed in the high-insulation and high-heat-insulation composite sheet used between lithium battery cells; the through holes are filled with aerogel; the high-insulation and high-heat-insulation composite sheet comprises a bottom plate, a cover plate and a partition plate fixedly connected between the bottom plate and the cover plate, and the high-insulation and high-heat-insulation composite sheet is prepared from 1-3 wt% of aramid nanofibers, 5-10 wt% of superfine mica powder, 2-5 wt% of nanosilicon dioxide, 10-25 wt% of hollow glass beads, 4-8 wt% of a plasticizer and the balance of high-temperature-resistant resin. The power battery module has good flame-retardant, insulating and heat-insulating effects, the thermal runaway protection performance of the power battery module can be improved, then the driving safety performance of a new energy automobile can be improved, the advantage of light weight is achieved, and the voyage of the new energy automobile can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of thermal runaway protection materials for lithium battery modules, and in particular to a high-insulation and high-heat-insulation composite sheet material used between lithium battery cells and a preparation process thereof. Background Art

[0002] The power battery module is one of the core components of new energy vehicles and one of the core competitiveness of new energy vehicles. The thermal runaway protection performance of the power battery module determines the driving safety of new energy vehicles and has always been the focus of attention of consumers. How to improve the thermal runaway protection performance of the power battery module is a key research issue for new energy vehicle manufacturers.

[0003] At present, the structure of the heat insulation buffer material between lithium battery cells in the power battery module is as follows: mica paper / butyl rubber / mica paper. Although it has good flame retardant and fireproof performance and shock absorption, noise reduction and heat insulation effect, the overall thermal conductivity is still between 0.2-0.3W / (m·K), the overall heat insulation performance is relatively general, and the overall density is 2.2-2.7g / cm 3 In the meantime, it has gradually been unable to meet the demand for lightweight power battery modules. Summary of the invention

[0004] In order to solve the technical bottlenecks existing in the above-mentioned prior art, the present application provides a high-insulation and high-heat-insulation composite sheet for use between lithium battery cells and a preparation process thereof.

[0005] The high insulation and high heat insulation composite sheet for lithium battery cells provided in the present application is realized by the following scheme: A high-insulation and high-heat-insulation composite sheet used between lithium battery cells is formed with a through hole inside for heat insulation and noise reduction; the through hole is filled with aerogel; the high-insulation and high-heat-insulation composite sheet comprises a base plate, a cover plate and a partition plate fixedly connected between the base plate and the cover plate, the thickness of the base plate and the cover plate are both 0.25-0.40mm; the spacing between the base plate and the cover plate is 0.60-0.80mm; the thickness of the partition plate is 0.10-0.25mm; the high-insulation and high-heat-insulation composite sheet is made of high-insulation and high-heat-insulation composite masterbatch; the high-insulation and high-heat-insulation composite masterbatch is made of the following materials in mass percentage: 1-3wt% aramid nanofiber, 5-10wt% ultrafine mica powder, 2-5wt% nano silicon dioxide, 10-25% hollow glass microspheres, 4-8wt% plasticizer, and the balance is high temperature resistant resin.

[0006] The high-insulation and high-thermal insulation composite sheet in the present application has good flame retardant insulation and heat insulation effects. It is used between lithium battery cells to form a power battery module, which can improve the thermal runaway protection performance of the power battery module, and thus improve the driving safety performance of new energy vehicles. It also has the advantage of being lightweight and can improve the range of new energy vehicles.

[0007] Preferably, the high temperature resistant resin is PI resin or PPS resin; the particle size of the ultrafine mica powder is ≤6.5 μm; the particle size of the hollow glass microspheres is ≤8.0 μm; and the particle size of the nano-silicon dioxide is 50-200 nm.

[0008] Preferably, the thickness of the bottom plate and the cover plate is 0.25-0.30mm; the spacing between the bottom plate and the cover plate is 0.75-0.80mm; the spacing between adjacent partition plates is 0.60-1.2mm; the thickness of the partition plate is 0.15-0.20mm; the partition plate is I-shaped, one end is fixedly connected to the cover plate and the other end is integrally formed with the bottom plate; the ultrafine mica powder is discharged from a 5000 mesh sieve; the hollow glass microspheres are discharged from a 5000 mesh sieve.

[0009] By adopting the above technical solution, the flame retardant, insulating and heat-insulating properties of the prepared high-insulation and high-heat-insulating composite sheet can be guaranteed, while providing a material basis for the overall lightweight design, thereby reducing the overall mass of the power battery module and increasing endurance.

[0010] Preferably, the high-insulation and high-thermal-insulation composite masterbatch is made of 2.4-2.6wt% of aramid nanofiber, 7.5-8.5wt% of ultrafine mica powder, 2.5-3.0wt% of nano-silicon dioxide, 16-20% of hollow glass microspheres, 4-5wt% of hyperbranched PPS resin, and the remainder is injection molding grade PPS resin; the high-insulation and high-thermal-insulation composite masterbatch is made into a semi-finished high-insulation and high-thermal-insulation composite sheet, and the semi-finished high-insulation and high-thermal-insulation composite sheet includes a base plate and a partition plate.

[0011] Preferably, the cover plate is made of the following materials in percentage by mass: 1-3wt% aramid nanofiber, 2-5wt% nano-silicon dioxide, 2-5wt% nano-aluminum hydroxide, 10-25% hollow glass microspheres, 4-8wt% plasticizer, and the remainder is PI resin.

[0012] By adopting the above technical scheme, the flame retardant, insulating and heat insulating properties of the high-insulating and high-heat-insulating composite sheet can be guaranteed while improving the overall processing performance, reducing the overall production cost, and facilitating industrial promotion and application.

[0013] Preferably, the preparation method of the ultrafine mica powder is as follows: S1, mica powder is successively crushed by roller pressing, ball milling, and sieved through a sieve to obtain ultrafine mica powder ≥ 2000 mesh; S2, 8-12 parts of superfine mica powder sieved through a mesh of ≥2000 and 1 part of bamboo-shaped boron nitride nanotubes are uniformly mixed to obtain a mixture, the mixture is mixed with anhydrous ethanol at a ratio of 1:(0.42-0.48), a ball-to-material ratio of 8-12, wet-milled at 1600-1800 rpm for 2-4 h, and dried to obtain modified BN@superfine mica powder; S3, taking 3-6 parts of the obtained modified BN@ultrafine mica powder and 100 parts of a 0.5-5wt% aqueous solution of methacryloxysilane for ultrasonic dispersion treatment for 0.5-2h, the ultrasonic frequency is 40-60kHz, the ultrasonic power is 600-1200W, and the surface modified BN@ultrafine mica powder is obtained by leaching and drying.

[0014] Preferably, in S2, 9 parts of 5000 mesh sieved ultrafine mica powder and 1 part of bamboo-shaped boron nitride nanotubes are evenly mixed to obtain a mixture, the obtained mixture is mixed with anhydrous ethanol at a ratio of 1:0.45, the ball-to-material ratio is 10, and the ball milling is carried out at 1800 rpm for 4 hours, and the modified BN@ultrafine mica powder is obtained by drying.

[0015] The finished surface-modified BN@ultrafine mica powder prepared by adopting the above technical solution can improve the yield of high-insulation and high-thermal insulation composite sheets, thereby reducing the overall production cost and facilitating industrial promotion and application.

[0016] The present application provides a preparation process for a high-insulation and high-heat-insulation composite sheet for lithium battery cells, which is achieved through the following technical solutions: A preparation process of a high-insulation and high-heat-insulation composite sheet for lithium battery cells, comprising the following steps: Step 1: 10-20 parts of aramid nanofibers, 78-88 parts of high temperature resistant resin, and 1-2 parts of coupling agent are mixed evenly and then put into a twin-screw extruder for melt extrusion, wire drawing, water cooling, granulation, and drying to obtain aramid nanofiber masterbatch; Step 2: Put aramid nanofiber masterbatch, ultrafine mica powder, nano silicon dioxide, hollow glass microspheres, plasticizer, and high temperature resistant resin into a twin-screw extruder for melt extrusion, wire drawing, water cooling, granulation, and drying to obtain high insulation and high thermal insulation composite masterbatch; the content of aramid nanofiber in the high insulation and high thermal insulation composite masterbatch is 1-3wt%; Step 3, putting the high-insulation and high-thermal insulation composite masterbatch into a twin-screw extruder for melt extrusion and injection molding to obtain a semi-finished high-insulation and high-thermal insulation composite sheet, wherein the semi-finished high-insulation and high-thermal insulation composite sheet is composed of a bottom plate and a partition plate, and one end of the partition plate is integrally formed on the upper surface of the bottom plate; at the same time, putting the high-insulation and high-thermal insulation composite masterbatch into a twin-screw extruder for melt extrusion and injection molding to obtain a cover plate; Step 4: After filling the through holes of the semi-finished high-insulation and high-heat-insulation composite sheet with aerogel, the cover plate is fixedly connected to one end of the partition plate facing away from the upper surface of the bottom plate to obtain a finished high-insulation and high-heat-insulation composite sheet.

[0017] The preparation process provided in this application is relatively simple, has low implementation difficulty, and is easy to implement for industrial production.

[0018] Preferably, in step four, the semi-finished high-insulation and high-thermal insulation composite sheet is first subjected to low-temperature plasma treatment: ozone low-temperature plasma treatment is performed at 0-4°C for 240-320s, and after the plasma treatment is completed, the semi-finished high-insulation and high-thermal insulation composite sheet is sealed at both ends with a mold, and the aerogel precursor liquid is injected into the through holes of the semi-finished high-insulation and high-thermal insulation composite sheet, and the aerogel precursor liquid is hydrolyzed and polycondensed at 120±5°C for 20-40h and then cooled to room temperature. The through holes of the semi-finished high-insulation and high-thermal insulation composite sheet can be filled with aerogel by washing and drying, and then the cover plate is fixedly connected to one end of the upper surface of the partition plate facing away from the bottom plate to obtain a finished high-insulation and high-thermal insulation composite sheet.

[0019] By adopting the above technical solution, the service life and stability of the finished high-insulation and high-heat-insulating composite sheet can be improved.

[0020] Preferably, the aerogel is a flexible aerogel, and the density of the flexible aerogel is 5-200 mg / cm3.

[0021] By adopting the above technical solution, the thermal insulation and sound insulation performance of the finished high-insulation and high-thermal insulation composite sheet can be improved, and at the same time the overall weight of the finished high-insulation and high-thermal insulation composite sheet can be reduced, further meeting the lightweight requirements of new energy vehicles.

[0022] In summary, this application has the following advantages: 1. The high-insulation and high-thermal insulation composite sheet in this application has good flame retardant insulation and heat insulation effects. It is used between lithium battery cells to form a power battery module, which can improve the thermal runaway protection performance of the power battery module, and thus improve the driving safety performance of new energy vehicles. It also has the advantage of being lightweight and can improve the range of new energy vehicles.

[0023] 2. The preparation process provided in this application is relatively simple, has low implementation difficulty, and is easy to implement for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 It is a schematic diagram of the overall structure of a high-insulation and high-heat-insulation composite sheet used between lithium battery cells in an embodiment of the present application.

[0025] In the figure, 10, through hole; 11, bottom plate; 12, cover plate; 13, partition plate; 2, aerogel. DETAILED DESCRIPTION

[0026] In order to further understand the present invention, embodiments of the present invention are described below in conjunction with examples, drawings and comparative examples.

[0027] Preparation Example 1: Preparation of hyperbranched PPS resin: Add 10 g of 3,4-dichlorothiophenol, 3.4 g of anhydrous potassium carbonate and 80 mL of N-methylpyrrolidone to a 250 mL three-necked bottle, heat to 150°C, and keep warm for 8.5 hours. After the product is washed and filtered with hydrochloric acid, tetrahydrofuran is added to dissolve, extracted with hexane, filtered and dried to obtain light brown hyperbranched PPS powder.

[0028] Preparation Example 2: Preparation method of nano-aramid fiber: Aramid nanofiber (ANFS) dispersion U51 was prepared by a proton donor-assisted deprotonation method. Specifically, 2 g of para-aramid PPTA fiber was weighed and placed in a mixed solution of 3 g KOH, 1.0 L DMSO and 40 mL deionized water. The solution was stirred in a water bath at 60 ° C for 3 h to obtain a deep red ANFS dispersion with a mass concentration of 2 g / L. Aramid nanofiber ANFS powder was obtained by nanofiltration.

[0029] Preparation Example 3: The preparation method of ultrafine mica powder is as follows: S1, 325 mesh phlogopite powder is successively crushed by roller pressing, ball milling and sieving to obtain 2000 mesh ultrafine mica powder; S2, 8 parts of 2000 mesh sieved ultrafine mica powder and 1 part of bamboo-shaped boron nitride nanotubes (bamboo-shaped boron nitride nanotubes produced by Angxing New Carbon Materials Changzhou Co., Ltd.) are mixed evenly to obtain a mixture, and the obtained mixture is wet-milled with anhydrous ethanol at a ratio of 1:0.42 and a ball-to-material ratio of 8 at 1600 rpm for 4 hours, and then dried to obtain modified BN@ultrafine mica powder; S3, take 3 parts of the modified BN@ultrafine mica powder obtained in S2 and 100 parts of a 2wt% aqueous solution of methacryloyloxysilane KH570 for ultrasonic dispersion treatment for 1 hour, the ultrasonic frequency is 44kHz, the ultrasonic power is 800W, drain and dry to obtain the finished surface modified BN@ultrafine mica powder.

[0030] The difference between Preparation Example 4 and Preparation Example 3 is that: S1, 325 mesh phlogopite powder is successively crushed by roller pressing, ball milling, and sieving to obtain 5000 mesh ultrafine mica powder.

[0031] The difference between Preparation Example 5 and Preparation Example 3 is that: S1, 325 mesh phlogopite powder is successively crushed by roller pressing, ball milling, and sieving to obtain 10000 mesh sieved ultrafine mica powder.

[0032] The difference between Preparation Example 6 and Preparation Example 3 is that: S2, 10 parts of 2000 mesh sieved ultrafine mica powder and 1 part of bamboo-shaped boron nitride nanotubes are mixed evenly to obtain a mixture, the obtained mixture is mixed with anhydrous ethanol at a ratio of 1:0.42, the ball-to-material ratio is 8, and the ball milling is carried out at 1600rpm for 4h, and the modified BN@ultrafine mica powder is obtained by drying.

[0033] The difference between Preparation Example 7 and Preparation Example 3 is that: S2, 12 parts of 2000 mesh sieved ultrafine mica powder and 1 part of bamboo-shaped boron nitride nanotubes are mixed evenly to obtain a mixture, the obtained mixture is mixed with anhydrous ethanol at a ratio of 1:0.42, the ball-to-material ratio is 8, and the ball milling is carried out at 1600rpm for 4h, and the modified BN@ultrafine mica powder is obtained by drying.

[0034] The difference between Preparation Example 8 and Preparation Example 3 is that: S2, 10 parts of 2000 mesh sieved ultrafine mica powder and 1 part of bamboo-shaped boron nitride nanotubes are mixed evenly to obtain a mixture, the obtained mixture is mixed with anhydrous ethanol at a ratio of 1:0.45, the ball-to-material ratio is 8, and the ball milling is carried out at 1600rpm for 4h, and the modified BN@ultrafine mica powder is obtained by drying.

[0035] The difference between Preparation Example 9 and Preparation Example 3 is that: S2, 10 parts of 2000 mesh sieved ultrafine mica powder and 1 part of bamboo-shaped boron nitride nanotubes are mixed evenly to obtain a mixture, the obtained mixture is mixed with anhydrous ethanol at a ratio of 1:0.48, the ball-to-material ratio is 8, and it is wet-milled at 1600rpm for 4h, and then dried to obtain modified BN@ultrafine mica powder.

[0036] The difference between Preparation Example 10 and Preparation Example 3 is that: S2, 10 parts of 2000 mesh sieved ultrafine mica powder and 1 part of bamboo-shaped boron nitride nanotubes are mixed evenly to obtain a mixture, the obtained mixture is mixed with anhydrous ethanol at a ratio of 1:0.42, the ball-to-material ratio is 10, and the ball milling is carried out at 1600rpm for 4h, and the modified BN@ultrafine mica powder is obtained by drying.

[0037] The difference between Preparation Example 11 and Preparation Example 3 is that: S2, 10 parts of 2000 mesh sieved ultrafine mica powder and 1 part of bamboo-shaped boron nitride nanotubes are mixed evenly to obtain a mixture, the obtained mixture is mixed with anhydrous ethanol at a ratio of 1:0.42, the ball-to-material ratio is 12, and the ball-milling is carried out at 1600rpm for 4h, and the modified BN@ultrafine mica powder is obtained by drying.

[0038] The difference between Preparation Example 12 and Preparation Example 3 is that: S2, 9 parts of 5000 mesh sieved ultrafine mica powder and 1 part of bamboo-shaped boron nitride nanotubes are mixed evenly to obtain a mixture, the obtained mixture is mixed with anhydrous ethanol at a ratio of 1:0.45, the ball-to-material ratio is 10, and it is wet-milled at 1800rpm for 4h, and then dried to obtain modified BN@ultrafine mica powder.

[0039] The difference between Preparation Example 13 and Preparation Example 3 is that: S1, 325 mesh phlogopite powder is successively crushed by roller pressing, ball milling, and sieving to obtain 1340 mesh ultrafine mica powder.

[0040] The difference between Preparation Example 14 and Preparation Example 3 is that: S2, 7 parts of 2000 mesh sieved ultrafine mica powder and 1 part of bamboo-shaped boron nitride nanotubes are mixed evenly to obtain a mixture, the obtained mixture is mixed with anhydrous ethanol at a ratio of 1:0.42, the ball-to-material ratio is 8, and the mixture is wet-milled at 1600rpm for 4h, and then dried to obtain modified BN@ultrafine mica powder.

[0041] The difference between Preparation Example 15 and Preparation Example 3 is that: S2, 15 parts of 2000 mesh sieved ultrafine mica powder and 1 part of bamboo-shaped boron nitride nanotubes are mixed evenly to obtain a mixture, the obtained mixture is mixed with anhydrous ethanol at a ratio of 1:0.42, the ball-to-material ratio is 8, and the mixture is wet-milled at 1600rpm for 4h, and then dried to obtain modified BN@ultrafine mica powder.

[0042] The difference between Preparation Example 16 and Preparation Example 3 is that: S2, 10 parts of 2000 mesh sieved ultrafine mica powder and 1 part of bamboo-shaped boron nitride nanotubes are mixed evenly to obtain a mixture, the obtained mixture is mixed with anhydrous ethanol at a ratio of 1:0.40, the ball-to-material ratio is 8, and it is wet-milled at 1600rpm for 4h, and then dried to obtain modified BN@ultrafine mica powder.

[0043] The difference between Preparation Example 17 and Preparation Example 3 is that: S2, 10 parts of 2000 mesh sieved ultrafine mica powder and 1 part of bamboo-shaped boron nitride nanotubes are mixed evenly to obtain a mixture, the obtained mixture is mixed with anhydrous ethanol at a ratio of 1:0.50, the ball-to-material ratio is 8, and it is wet-milled at 1600rpm for 4h, and then dried to obtain modified BN@ultrafine mica powder.

[0044] The difference between Preparation Example 18 and Preparation Example 3 is that: S2, 10 parts of 2000 mesh sieved ultrafine mica powder and 1 part of bamboo-shaped boron nitride nanotubes are mixed evenly to obtain a mixture, the obtained mixture is mixed with anhydrous ethanol at a ratio of 1:0.42, the ball-to-material ratio is 6, and the mixture is wet-milled at 1600rpm for 4h, and then dried to obtain modified BN@ultrafine mica powder.

[0045] The difference between Preparation Example 19 and Preparation Example 3 is that: S2, 10 parts of 2000 mesh sieved ultrafine mica powder and 1 part of bamboo-shaped boron nitride nanotubes are mixed evenly to obtain a mixture, the obtained mixture is mixed with anhydrous ethanol at a ratio of 1:0.42, the ball-to-material ratio is 15, and it is wet-milled at 1600rpm for 4h, and then dried to obtain modified BN@ultrafine mica powder.

[0046] The difference between Preparation Example 20 and Preparation Example 3 is that the preparation method of ultrafine mica powder is as follows: S1, 325 mesh phlogopite powder is successively crushed by roller pressing, ball milling and sieving to obtain 2000 mesh ultrafine mica powder; S2, take 3 parts of 2000 mesh sieved ultrafine mica powder and 100 parts of 2wt% methacryloyloxysilane KH570 aqueous solution for ultrasonic dispersion treatment for 1 hour, ultrasonic frequency 44kHz, ultrasonic power 800W, drain and dry to obtain the finished surface modified BN@ultrafine mica powder. Example

[0047] refer to Figure 1 A high-insulation and high-heat-insulation composite sheet for use between lithium battery cells is formed with a through hole 10 for heat insulation and noise reduction; the through hole 10 is filled with aerogel 2. The high-insulation and high-heat-insulation composite sheet includes a base plate 11, a cover plate 12, and a partition plate 13 fixedly connected between the base plate 11 and the cover plate 12. The thickness of the base plate 11 and the cover plate 12 is 0.25-0.40mm. The spacing between the base plate 11 and the cover plate 12 is 0.60-0.80mm. The thickness of the partition plate 13 is 0.10-0.25mm. Preferably, the thickness of the base plate 11 and the cover plate 12 is 0.25-0.30mm. The spacing between the base plate 11 and the cover plate 12 is 0.75-0.80mm. The spacing between adjacent partition plates 13 is 0.60-1.2mm. The thickness of the partition plate 13 is 0.15-0.20mm. The partition plate 13 is in an I-shape, one end of which is fixedly connected to the cover plate 12 and the other end of which is integrally formed with the bottom plate 11 .

[0048] The high-insulation and high-heat-insulation composite sheet is made of high-insulation and high-heat-insulation composite masterbatch; the high-insulation and high-heat-insulation composite masterbatch is made of the following materials in percentage by mass: 1-3wt% aramid nanofiber, 5-10wt% ultrafine mica powder, 2-5wt% nano silicon dioxide, 10-25% hollow glass microspheres, 4-8wt% plasticizer, and the balance is high-temperature resistant resin.

[0049] The high temperature resistant resin is PI resin or PPS resin.

[0050] The particle size of the ultrafine mica powder is ≤6.5 μm. Preferably, the ultrafine mica powder is sieved through a 5000 mesh screen.

[0051] Further preferably, the preparation method of ultrafine mica powder is as follows: S1, mica powder is successively crushed by roller pressing, ball milling, and sieved through a sieve to obtain ultrafine mica powder ≥ 2000 mesh; S2, 8-12 parts of superfine mica powder sieved through a mesh of ≥2000 and 1 part of bamboo-shaped boron nitride nanotubes are uniformly mixed to obtain a mixture, the mixture is mixed with anhydrous ethanol at a ratio of 1:(0.42-0.48), a ball-to-material ratio of 8-12, wet-milled at 1600-1800 rpm for 2-4 h, and dried to obtain modified BN@superfine mica powder; Preferably, S2, 9 parts of 5000 mesh sieved ultrafine mica powder and 1 part of bamboo-shaped boron nitride nanotubes are mixed evenly to obtain a mixture, the obtained mixture is mixed with anhydrous ethanol at a ratio of 1:0.45, the ball-to-material ratio is 10, and the mixture is wet-milled at 1800 rpm for 4 hours, and dried to obtain modified BN@ultrafine mica powder; S3, taking 3-6 parts of the obtained modified BN@ultrafine mica powder and 100 parts of a 0.5-5wt% aqueous solution of methacryloxysilane for ultrasonic dispersion treatment for 0.5-2h, the ultrasonic frequency is 40-60kHz, the ultrasonic power is 600-1200W, and the surface modified BN@ultrafine mica powder is obtained by leaching and drying.

[0052] The particle size of the hollow glass microspheres is ≤8.0 μm. Preferably, the hollow glass microspheres are sieved through a 5000 mesh screen.

[0053] The particle size of nano-silicon dioxide is 50-200nm.

[0054] Preferably, the high-insulation and high-heat-insulation composite masterbatch is made of 2.4-2.6wt% aramid nanofiber, 7.5-8.5wt% ultrafine mica powder, 2.5-3.0wt% nano-silicon dioxide, 16-20% hollow glass microspheres, 4-5wt% hyperbranched PPS resin, and the balance is injection-molding grade PPS resin. The high-insulation and high-heat-insulation composite masterbatch is made into a semi-finished high-insulation and high-heat-insulation composite sheet, and the semi-finished high-insulation and high-heat-insulation composite sheet includes a bottom plate 11 and a partition plate 13. The cover plate 12 is made of the following materials in mass percentage: 1-3wt% aramid nanofiber, 2-5wt% nano-silicon dioxide, 2-5wt% nano-aluminum hydroxide, 10-25% hollow glass microspheres, 4-8wt% plasticizer, and the balance is PI resin.

[0055] refer to Figure 1 A preparation process of a high-insulation and high-heat-insulation composite sheet for lithium battery cells, comprising the following steps: Step 1: 10-20 parts of aramid nanofibers, 78-88 parts of high temperature resistant resin, and 1-2 parts of coupling agent are mixed evenly and then put into a twin-screw extruder for melt extrusion, wire drawing, water cooling, granulation, and drying to obtain aramid nanofiber masterbatch; Step 2: Putting aramid nanofiber masterbatch, ultrafine mica powder, nano silicon dioxide, hollow glass microspheres, plasticizer, and high temperature resistant resin into a twin-screw extruder for melt extrusion, wire drawing, water cooling, granulation, and drying to obtain high insulation and high thermal insulation composite masterbatch; the content of aramid nanofiber in the high insulation and high thermal insulation composite masterbatch is 1-3wt%; Step 3: Put the high-insulation and high-thermal insulation composite masterbatch into a twin-screw extruder for melt extrusion and injection molding to obtain a semi-finished high-insulation and high-thermal insulation composite sheet, wherein the semi-finished high-insulation and high-thermal insulation composite sheet is composed of a bottom plate 11 and a partition plate 13, and one end of the partition plate 13 is integrally formed on the upper surface of the bottom plate 11; at the same time, put the high-insulation and high-thermal insulation composite masterbatch into a twin-screw extruder for melt extrusion and injection molding to obtain a cover plate 12; Step 4: After the aerogel 2 is filled into the through hole 10 of the semi-finished high-insulation and high-heat-insulation composite sheet, the cover plate 12 is fixedly connected to the end of the partition plate 13 facing away from the upper surface of the bottom plate 11, so as to obtain a finished high-insulation and high-heat-insulation composite sheet; Preferably, in step 4, the semi-finished high-insulation and high-heat-insulation composite sheet is first subjected to low-temperature plasma treatment: ozone low-temperature plasma treatment is performed at 0-4°C for 240-320s, and after the plasma treatment is completed, the semi-finished high-insulation and high-heat-insulation composite sheet is sealed at both ends with a mold, and the aerogel precursor liquid is injected into the through hole 10 of the semi-finished high-insulation and high-heat-insulation composite sheet, and the semi-finished high-insulation and high-heat-insulation composite sheet is hydrolyzed and polycondensed at 120±5°C for 20-40h and then cooled to room temperature, washed with water, and dried to fill the through hole 10 of the semi-finished high-insulation and high-heat-insulation composite sheet with aerogel 2, where aerogel 2 is a flexible aerogel, and the density of the flexible aerogel is 5-200mg / cm 3 , and then the cover plate 12 is fixedly connected to the end of the partition plate 13 facing away from the upper surface of the bottom plate 11 to obtain a finished high-insulation and high-heat-insulation composite sheet.

[0056] Example 1: Reference Figure 1 A high insulation and high heat insulation composite sheet for lithium battery cells has a through hole 10 formed inside for heat insulation and noise reduction. The through hole 10 is filled with aerogel 2. The aerogel 2 is a flexible aerogel with a density of 50 mg / cm 3 The high insulation and high heat insulation composite sheet comprises a bottom plate 11, a cover plate 12 and a partition plate 13. The partition plate 13 is I-shaped, one end of which is fixedly connected to the cover plate 12 and the other end is integrally formed with the bottom plate 11.

[0057] The thickness of the bottom plate 11 and the cover plate 12 are both 0.30 mm. The spacing between the bottom plate 11 and the cover plate 12 is 0.80 mm. The spacing between adjacent partition plates 13 is 1.0 mm. The thickness of the partition plate 13 is 0.20 mm.

[0058] The overall dimensions of the high insulation and high thermal insulation composite sheet are 24.0cm long*18.2cm wide*1.4mm thick.

[0059] The bottom plate 11, the cover plate 12 and the partition plate 13 are all made of high-insulation and high-heat-insulation composite masterbatch.

[0060] The high-insulation and high-heat-insulation composite masterbatch is made of the following materials in percentage by mass: 1wt% of the aramid nanofiber in Preparation Example 2, 5wt% of the ultrafine mica powder in Preparation Example 3, 2wt% of nano-silicon dioxide (Evonik AEROSIL 200 hydrophilic white carbon black A200), 17% of hollow glass microspheres (hollow glass microspheres customized by China Science Huaxing New Materials Co., Ltd. with a particle size of 2-5μm), 5wt% of the hyperbranched PPS resin in Preparation Example 1, and the remainder is PPS resin (Japan Polyplastics, brand 0220A9, PPS pure resin, injection molding grade, melt viscosity 260Pa*s at 310°C).

[0061] refer to Figure 1 A preparation process of a high-insulation and high-heat-insulation composite sheet for lithium battery cells, comprising the following steps: Step 1, 15 parts of the aramid nanofibers in Preparation Example 2, 84 parts of PPS resin 0220A9, and 1 part of KH570 coupling agent are placed in a high-speed dispersion kettle and mixed and dispersed at 600 rpm for 4 hours, and then the resulting mixture is put into a twin-screw extruder for melt extrusion, and the four-stage temperature of the barrel end temperature is set to 300°C, 310°C, 320°C, and 320°C in sequence, the nozzle temperature is 320°C, the injection pressure is 88MPa, the injection speed is 40mm / s, and the screw rotation speed is 50rpm. The resulting molten extrusion material is subjected to wire drawing, water cooling, granulation, and drying to obtain an aramid nanofiber masterbatch with a particle size of 1-1.2mm; Step 2, 6.67g aramid nanofiber masterbatch, 50g ultrafine mica powder in Preparation Example 3, 20g nano-silicon dioxide A200, 170g hollow glass microspheres, 50g hyperbranched PPS resin in Preparation Example 1, and 694.33g PPS resin 0220A9 are put into a twin-screw extruder for melt extrusion, and the four-stage temperature of the barrel end temperature is set to 300°C, 316°C, 328°C, and 328°C in sequence, the nozzle temperature is 328°C, the injection pressure is 95MPa, the injection speed is 48mm / s, and the screw rotation speed is 56rpm. The obtained molten extrusion material is drawn, water-cooled, granulated, and dried to obtain a high-insulation and high-heat-insulation composite masterbatch with a particle size of 1-1.2mm; Step 3, putting the high-insulation and high-heat-insulation composite masterbatch into a twin-screw extruder for melt extrusion and injection molding: the four temperature sections of the barrel end temperature are set to 300°C, 316°C, 328°C, and 328°C in sequence, the nozzle temperature is 328°C, the injection pressure is 98MPa, the injection speed is 52mm / s, and the screw rotation speed is 52rpm to obtain a semi-finished high-insulation and high-heat-insulation composite sheet, which is composed of a bottom plate 11 and a partition plate 13, and one end of the partition plate 13 is integrally formed on the upper surface of the bottom plate 11; At the same time, the high insulation and high heat insulation composite masterbatch is put into a twin-screw extruder for melt extrusion and injection molding: the four temperature sections of the barrel end temperature are set to 300°C, 316°C, 328°C, and 328°C in sequence, the nozzle temperature is 328°C, the injection pressure is 98MPa, the injection speed is 52mm / s, and the screw rotation speed is 52rpm to obtain the cover plate 12; At the same time, the aerogel precursor liquid was prepared: 146.26g of allyldimethylmethoxysilane (CAS: 67681-66-7), 11.42g of allyltrimethylsilane (CAS: 762-72-1), and 12.1g of dibenzoyl peroxide (CAS: 94-36-0) were placed in a 1L custom reactor, nitrogen was introduced to remove oxygen in the system, and the mixture was mixed evenly under nitrogen protection, and the temperature was raised to 90°C for free radical polymerization reaction for 6h. After the material was cooled to 25°C in a water bath, 20g of tetramethylammonium hydroxide and 39.6g of distilled water were added to the reactor and mixed evenly to obtain a flexible aerogel precursor liquid; Step 4, first perform low-temperature plasma treatment on the semi-finished high-insulation and high-thermal insulation composite sheet: use ozone low-temperature plasma treatment for 300s at 0-4°C, and after completing the plasma treatment, use a mold to seal both ends of the semi-finished high-insulation and high-thermal insulation composite sheet, inject aerogel precursor liquid into the through hole 10 of the semi-finished high-insulation and high-thermal insulation composite sheet, hydrolyze and condense at 120°C for 24 hours, then cool to room temperature, wash and dry, and fill the through hole 10 of the semi-finished high-insulation and high-thermal insulation composite sheet with aerogel 2, finally fix the cover plate 12 to the end of the upper surface of the partition plate 13 facing away from the bottom plate 11 by ultrasonic welding, and the finished high-insulation and high-thermal insulation composite sheet can be obtained.

[0062] The difference between Example 2 and Example 1 is that the high-insulation and high-thermal insulation composite masterbatch is made of the following materials in percentage by mass: 2.0wt% of the aramid nanofiber in Preparation Example 2, 5wt% of the ultrafine mica powder in Preparation Example 3, 2wt% of nano-silica A200, 17% of hollow glass microspheres, 5wt% of the hyperbranched PPS resin in Preparation Example 1, and the remainder is PPS resin 0220A9.

[0063] The difference between Example 3 and Example 1 is that the high-insulation and high-thermal insulation composite masterbatch is made of the following materials in percentage by mass: 2.5wt% of the aramid nanofiber in Preparation Example 2, 5wt% of the ultrafine mica powder in Preparation Example 3, 2wt% of nano-silica A200, 17% of hollow glass microspheres, 5wt% of the hyperbranched PPS resin in Preparation Example 1, and the remainder is PPS resin 0220A9.

[0064] The difference between Example 4 and Example 1 is that the high-insulation and high-thermal insulation composite masterbatch is made of the following materials in percentage by mass: 3wt% of the aramid nanofiber in Preparation Example 2, 5wt% of the ultrafine mica powder in Preparation Example 3, 2wt% of nano-silica A200, 17% of hollow glass microspheres, 5wt% of the hyperbranched PPS resin in Preparation Example 1, and the remainder is PPS resin 0220A9.

[0065] The difference between Example 5 and Example 1 is that the high-insulation and high-thermal insulation composite masterbatch is made of the following materials in percentage by mass: 2.5wt% of the aramid nanofiber in Preparation Example 2, 8wt% of the ultrafine mica powder in Preparation Example 3, 2wt% of nano-silica A200, 17% of hollow glass microspheres, 5wt% of the hyperbranched PPS resin in Preparation Example 1, and the remainder is PPS resin 0220A9.

[0066] The difference between Example 6 and Example 1 is that the high-insulation and high-thermal insulation composite masterbatch is made of the following materials in percentage by mass: 2.5wt% of the aramid nanofiber in Preparation Example 2, 10wt% of the ultrafine mica powder in Preparation Example 3, 2wt% of nano-silica A200, 17% of hollow glass microspheres, 5wt% of the hyperbranched PPS resin in Preparation Example 1, and the remainder is PPS resin 0220A9.

[0067] The difference between Example 7 and Example 1 is that the high-insulation and high-thermal insulation composite masterbatch is made of the following materials in percentage by mass: 2.5wt% of the aramid nanofiber in Preparation Example 2, 8wt% of the ultrafine mica powder in Preparation Example 3, 3wt% of nano-silica A200, 17% of hollow glass microspheres, 5wt% of the hyperbranched PPS resin in Preparation Example 1, and the remainder is PPS resin 0220A9.

[0068] The difference between Example 8 and Example 1 is that the high-insulation and high-thermal insulation composite masterbatch is made of the following materials in percentage by mass: 2.5wt% of the aramid nanofiber in Preparation Example 2, 8wt% of the ultrafine mica powder in Preparation Example 3, 4wt% of nano-silica A200, 17% of hollow glass microspheres, 5wt% of the hyperbranched PPS resin in Preparation Example 1, and the remainder is PPS resin 0220A9.

[0069] The difference between Example 9 and Example 1 is that the high-insulation and high-thermal insulation composite masterbatch is made of the following materials in percentage by mass: 2.5wt% of the aramid nanofiber in Preparation Example 2, 8wt% of the ultrafine mica powder in Preparation Example 3, 5wt% of nano-silica A200, 17% of hollow glass microspheres, 5wt% of the hyperbranched PPS resin in Preparation Example 1, and the remainder is PPS resin 0220A9.

[0070] The difference between Example 10 and Example 1 is that the high-insulation and high-thermal insulation composite masterbatch is made of the following materials in percentage by mass: 2.5wt% of the aramid nanofiber in Preparation Example 2, 8wt% of the ultrafine mica powder in Preparation Example 3, 3wt% of nano-silica A200, 10% of hollow glass microspheres, 5wt% of the hyperbranched PPS resin in Preparation Example 1, and the remainder is PPS resin 0220A9.

[0071] The difference between Example 11 and Example 1 is that the high-insulation and high-thermal insulation composite masterbatch is made of the following materials in percentage by mass: 2.5wt% of the aramid nanofiber in Preparation Example 2, 8wt% of the ultrafine mica powder in Preparation Example 3, 3wt% of nano-silica A200, 20% of hollow glass microspheres, 5wt% of the hyperbranched PPS resin in Preparation Example 1, and the remainder is PPS resin 0220A9.

[0072] The difference between Example 12 and Example 1 is that the high-insulation and high-thermal insulation composite masterbatch is made of the following materials in percentage by mass: 2.5wt% of the aramid nanofiber in Preparation Example 2, 8wt% of the ultrafine mica powder in Preparation Example 3, 3wt% of nano-silicon dioxide A200, 25% of hollow glass microspheres, 5wt% of the hyperbranched PPS resin in Preparation Example 1, and the remainder is PPS resin 0220A9.

[0073] The difference between Example 13 and Example 1 is that the high-insulation and high-thermal-insulation composite masterbatch is made of the following materials in mass percentage: the high-insulation and high-thermal-insulation composite masterbatch is made of the following materials in mass percentage: 2.5wt% of the aramid nanofiber in Preparation Example 2, 8wt% of the ultrafine mica powder in Preparation Example 3, 3wt% of nano-silica A200, 20% of hollow glass microspheres, 4wt% of the hyperbranched PPS resin in Preparation Example 1, and the remainder is PPS resin 0220A9.

[0074] The difference between Example 14 and Example 1 is that the high-insulation and high-thermal-insulation composite masterbatch is made of the following materials in mass percentage: the high-insulation and high-thermal-insulation composite masterbatch is made of the following materials in mass percentage: 2.5wt% of the aramid nanofiber in Preparation Example 2, 8wt% of the ultrafine mica powder in Preparation Example 3, 3wt% of nano-silica A200, 20% of hollow glass microspheres, 6wt% of the hyperbranched PPS resin in Preparation Example 1, and the remainder is PPS resin 0220A9.

[0075] The difference between Example 15 and Example 1 is that the high-insulation and high-thermal-insulation composite masterbatch is made of the following materials in mass percentage: the high-insulation and high-thermal-insulation composite masterbatch is made of the following materials in mass percentage: 2.5wt% of the aramid nanofiber in Preparation Example 2, 8wt% of the ultrafine mica powder in Preparation Example 3, 3wt% of nano-silica A200, 20% of hollow glass microspheres, 7wt% of the hyperbranched PPS resin in Preparation Example 1, and the remainder is PPS resin 0220A9.

[0076] The difference between Example 16 and Example 1 is that the high-insulation and high-thermal-insulation composite masterbatch is made of the following materials in mass percentage: the high-insulation and high-thermal-insulation composite masterbatch is made of the following materials in mass percentage: 2.5wt% of the aramid nanofiber in Preparation Example 2, 8wt% of the ultrafine mica powder in Preparation Example 3, 3wt% of nano-silica A200, 20% hollow glass microspheres, 8wt% of the hyperbranched PPS resin in Preparation Example 1, and the remainder is PPS resin 0220A9.

[0077] The difference between Example 17 and Example 1 is that the ultrafine mica powder in Preparation Example 3 is replaced by the ultrafine mica powder in Preparation Example 4.

[0078] The difference between Example 18 and Example 1 is that the ultrafine mica powder in Preparation Example 3 is replaced by the ultrafine mica powder in Preparation Example 5.

[0079] The difference between Example 19 and Example 1 is that the ultrafine mica powder in Preparation Example 3 is replaced by the ultrafine mica powder in Preparation Example 6.

[0080] The difference between Example 20 and Example 1 is that the ultrafine mica powder in Preparation Example 3 is replaced by the ultrafine mica powder in Preparation Example 7.

[0081] The difference between Example 21 and Example 1 is that the ultrafine mica powder in Preparation Example 3 is replaced by the ultrafine mica powder in Preparation Example 8.

[0082] The difference between Example 22 and Example 1 is that the ultrafine mica powder in Preparation Example 3 is replaced by the ultrafine mica powder in Preparation Example 9.

[0083] The difference between Example 23 and Example 1 is that the ultrafine mica powder in Preparation Example 3 is replaced by the ultrafine mica powder in Preparation Example 10.

[0084] The difference between Example 24 and Example 1 is that the ultrafine mica powder in Preparation Example 3 is replaced by the ultrafine mica powder in Preparation Example 11.

[0085] The difference between Example 25 and Example 1 is that the ultrafine mica powder in Preparation Example 3 is replaced by the ultrafine mica powder in Preparation Example 12.

[0086] The difference between Example 26 and Example 1 is that the high-insulation and high-thermal insulation composite masterbatch is made of the following materials in percentage by mass: 2.5wt% of the aramid nanofiber in Preparation Example 2, 8wt% of the ultrafine mica powder in Preparation Example 12, 3wt% of nano-silica A200, 20% of hollow glass microspheres, 5wt% of the hyperbranched PPS resin in Preparation Example 1, and the remainder is PPS resin 0220A9.

[0087] The difference between Example 27 and Example 26 is that the bottom plate and the partition plate are integrally injection molded from high-insulation and high-heat-insulation composite masterbatch. The cover plate is made of the following materials in percentage by mass: 1wt% aramid nanofiber, 2wt% nano-silicon dioxide, 5wt% nano-aluminum hydroxide, 22% hollow glass microspheres, 5wt% of the hyperbranched PPS resin in Preparation Example 1, and the remainder is PI resin (Mitsui Chemicals PI 450). The obtained cover plate can be fixedly connected to one end of the partition plate facing away from the upper surface of the bottom plate by laser welding, and a finished high-insulation and high-heat-insulation composite sheet can be obtained.

[0088] The difference between Comparative Example 1 and Example 1 is that the high-insulation and high-heat-insulation composite masterbatch is made of 5wt% of the ultrafine mica powder in Preparation Example 3, 2wt% of nano-silicon dioxide A200, 17% of hollow glass microspheres, 5wt% of the hyperbranched PPS resin in Preparation Example 1, and the remainder is PPS resin 0220A9.

[0089] The difference between Comparative Example 2 and Example 1 is that the high-insulation and high-thermal insulation composite masterbatch is made of the following materials in percentage by mass: 0.5wt% of the aramid nanofiber in Preparation Example 2, 5wt% of the ultrafine mica powder in Preparation Example 3, 2wt% of nano-silica A200, 17% of hollow glass microspheres, 5wt% of the hyperbranched PPS resin in Preparation Example 1, and the remainder is PPS resin 0220A9.

[0090] The difference between Comparative Example 3 and Example 1 is that the high-insulation and high-thermal insulation composite masterbatch is made of the following materials in percentage by mass: 4wt% of the aramid nanofiber in Preparation Example 2, 5wt% of the ultrafine mica powder in Preparation Example 3, 2wt% of nano-silica A200, 17% of hollow glass microspheres, 5wt% of the hyperbranched PPS resin in Preparation Example 1, and the remainder is PPS resin 0220A9.

[0091] The difference between Comparative Example 4 and Example 1 is that the high-insulation and high-thermal insulation composite masterbatch is made of the following materials in percentage by mass: 2.5wt% of the aramid nanofiber in Preparation Example 2, 0wt% of the ultrafine mica powder in Preparation Example 3, 2wt% of nano-silica A200, 17% of hollow glass microspheres, 5wt% of the hyperbranched PPS resin in Preparation Example 1, and the remainder is PPS resin 0220A9.

[0092] The difference between Comparative Example 5 and Example 1 is that the high-insulation and high-thermal insulation composite masterbatch is made of the following materials in percentage by mass: 2.5wt% of the aramid nanofiber in Preparation Example 2, 3wt% of the ultrafine mica powder in Preparation Example 3, 2wt% of nano-silica A200, 17% of hollow glass microspheres, 5wt% of the hyperbranched PPS resin in Preparation Example 1, and the remainder is PPS resin 0220A9.

[0093] The difference between Comparative Example 6 and Example 1 is that the high-insulation and high-thermal insulation composite masterbatch is made of the following materials in percentage by mass: 2.5wt% of the aramid nanofiber in Preparation Example 2, 12wt% of the ultrafine mica powder in Preparation Example 3, 2wt% of nano-silica A200, 17% of hollow glass microspheres, 5wt% of the hyperbranched PPS resin in Preparation Example 1, and the remainder is PPS resin 0220A9.

[0094] The difference between Comparative Example 7 and Example 1 is that the high-insulation and high-thermal insulation composite masterbatch is made of the following materials in percentage by mass: 2.5wt% of the aramid nanofiber in Preparation Example 2, 8wt% of the ultrafine mica powder in Preparation Example 3, 0wt% of nano-silica A200, 17% of hollow glass microspheres, 5wt% of the hyperbranched PPS resin in Preparation Example 1, and the remainder is PPS resin 0220A9.

[0095] The difference between Comparative Example 8 and Example 1 is that the high-insulation and high-thermal insulation composite masterbatch is made of the following materials in percentage by mass: 2.5wt% of the aramid nanofiber in Preparation Example 2, 8wt% of the ultrafine mica powder in Preparation Example 3, 1wt% of nano-silica A200, 17% of hollow glass microspheres, 5wt% of the hyperbranched PPS resin in Preparation Example 1, and the remainder is PPS resin 0220A9.

[0096] The difference between Comparative Example 9 and Example 1 is that the high-insulation and high-thermal insulation composite masterbatch is made of the following materials in percentage by mass: 2.5wt% of the aramid nanofiber in Preparation Example 2, 8wt% of the ultrafine mica powder in Preparation Example 3, 6wt% of nano-silica A200, 17% of hollow glass microspheres, 5wt% of the hyperbranched PPS resin in Preparation Example 1, and the remainder is PPS resin 0220A9.

[0097] The difference between Comparative Example 10 and Example 1 is that the high-insulation and high-thermal insulation composite masterbatch is made of the following materials in percentage by mass: 2.5wt% of the aramid nanofiber in Preparation Example 2, 8wt% of the ultrafine mica powder in Preparation Example 3, 3wt% of nano-silica A200, 0% of hollow glass microspheres, 5wt% of the hyperbranched PPS resin in Preparation Example 1, and the remainder is PPS resin 0220A9.

[0098] The difference between Comparative Example 11 and Example 1 is that the high-insulation and high-thermal insulation composite masterbatch is made of the following materials in percentage by mass: 2.5wt% of the aramid nanofiber in Preparation Example 2, 8wt% of the ultrafine mica powder in Preparation Example 3, 3wt% of nano-silica A200, 8% of hollow glass microspheres, 5wt% of the hyperbranched PPS resin in Preparation Example 1, and the remainder is PPS resin 0220A9.

[0099] The difference between Comparative Example 12 and Example 1 is that the high-insulation and high-thermal insulation composite masterbatch is made of the following materials in percentage by mass: 2.5wt% of the aramid nanofiber in Preparation Example 2, 8wt% of the ultrafine mica powder in Preparation Example 3, 3wt% of nano-silica A200, 28% of hollow glass microspheres, 5wt% of the hyperbranched PPS resin in Preparation Example 1, and the remainder is PPS resin 0220A9.

[0100] The difference between Comparative Example 13 and Example 1 is that the high-insulation high-heat-insulation composite masterbatch is made of the following materials by mass percentage: 2.5wt% of the aramid nanofiber in Preparation Example 2, 8wt% of the ultrafine mica powder in Preparation Example 3, 3wt% of nano-silicon dioxide A200, 20% of hollow glass microspheres, 0wt% of the hyperbranched PPS resin in Preparation Example 1, and the balance is PPS resin 0220A9. The yield rate of the obtained high-insulation high-heat-insulation composite sheet is less than 70%, and the degree of industrialization is low.

[0101] The difference between Comparative Example 14 and Example 1 is that the high-insulation high-heat-insulation composite masterbatch is made of the following materials by mass percentage: 2.5wt% of the aramid nanofiber in Preparation Example 2, 8wt% of the ultrafine mica powder in Preparation Example 3, 3wt% of nano-silicon dioxide A200, 20% of hollow glass microspheres, 2wt% of the hyperbranched PPS resin in Preparation Example 1, and the balance is PPS resin 0220A9. The yield rate of the obtained high-insulation high-heat-insulation composite sheet is less than 80%, and the degree of industrialization is low.

[0102] The difference between Comparative Example 15 and Example 1 is that the high-insulation and high-thermal-insulation composite masterbatch is made of the following materials in mass percentage: the high-insulation and high-thermal-insulation composite masterbatch is made of the following materials in mass percentage: 2.5wt% of the aramid nanofiber in Preparation Example 2, 8wt% of the ultrafine mica powder in Preparation Example 3, 3wt% of nano-silica A200, 20% of hollow glass microspheres, 10wt% of the hyperbranched PPS resin in Preparation Example 1, and the balance is PPS resin 0220A9.

[0103] The difference between Comparative Example 16 and Example 1 is that the ultrafine mica powder in Preparation Example 3 is replaced by the ultrafine mica powder in Preparation Example 13. The yield rate of the obtained high-insulation and high-heat-insulation composite sheet is less than 70%, and the degree of industrialization is low.

[0104] The difference between Comparative Example 17 and Example 1 is that the ultrafine mica powder in Preparation Example 3 is replaced by the ultrafine mica powder in Preparation Example 14.

[0105] The difference between Comparative Example 18 and Example 1 is that the ultrafine mica powder in Preparation Example 3 is replaced by the ultrafine mica powder in Preparation Example 15.

[0106] The difference between Comparative Example 19 and Example 1 is that the ultrafine mica powder in Preparation Example 3 is replaced by the ultrafine mica powder in Preparation Example 16.

[0107] The difference between Comparative Example 20 and Example 1 is that the ultrafine mica powder in Preparation Example 3 is replaced by the ultrafine mica powder in Preparation Example 17.

[0108] The difference between Comparative Example 21 and Example 1 is that the ultrafine mica powder in Preparation Example 3 is replaced by the ultrafine mica powder in Preparation Example 18.

[0109] The difference between Comparative Example 22 and Example 1 is that the ultrafine mica powder in Preparation Example 3 is replaced by the ultrafine mica powder in Preparation Example 19.

[0110] The difference between Comparative Example 23 and Example 1 is that the ultrafine mica powder in Preparation Example 3 is replaced by the ultrafine mica powder in Preparation Example 20.

[0111] Performance test: 1. Density is measured by volume method. 2. Flame retardant performance is measured according to UL-94. 3. Thermal conductivity is measured according to GB / T 10297-2015 "Determination of thermal conductivity of non-metallic solid materials - Hot wire method". 4. Electrical strength test method: measured according to GB / T 1408.1-2006 "Electrical strength test method for insulating materials - Part 1: Test under power frequency". 5. Tensile properties are measured according to ISO 527-2.

[0112] Table 1: Test parameters of high insulation and high heat insulation composite sheets in Examples 1-27 and Comparative Examples 1-23

[0113] Combining Examples 1-4 and Comparative Examples 1-3 with Table 1, it can be seen that the aramid nanofiber filler in the high-insulation and high-heat-insulation composite masterbatch is preferably controlled at 1-3wt%, which ensures the comprehensive performance of the high-insulation and high-heat-insulation composite sheet while reducing production costs.

[0114] Combining Examples 3, 5-6 and Comparative Examples 4-6 and Table 1, it can be seen that the addition amount of ultrafine mica powder in the high-insulation and high-thermal insulation composite masterbatch is preferably controlled to be 5-10wt%, which ensures the comprehensive performance of the high-insulation and high-thermal insulation composite sheet while reducing production costs.

[0115] Combining Examples 5, 7-9 and Comparative Examples 7-9 and Table 1, it can be seen that the addition amount of nano-silicon dioxide A200 in the high-insulation and high-thermal insulation composite masterbatch is preferably controlled at 2-5wt%, which ensures the comprehensive performance of the high-insulation and high-thermal insulation composite sheet while reducing production costs.

[0116] It can be seen from Examples 7, 10-12 and Comparative Examples 10-12 and Table 1 that the amount of hollow glass microspheres added to the high-insulation and high-thermal insulation composite masterbatch is preferably controlled at 10-25 wt%, preferably in the range of 17-20 wt%, which can ensure the thermal insulation and noise reduction performance and good mechanical properties of the high-insulation and high-thermal insulation composite sheet while reducing the overall production cost.

[0117] Combining Examples 11, 13-16 and Comparative Examples 13-16 and Table 1, it can be seen that the amount of hyperbranched PPS resin added in the high-insulation and high-heat-insulation composite masterbatch is preferably controlled to be 4-8wt%, preferably 4-5wt%. The addition of hyperbranched PPS resin affects the overall processing performance and yield rate. Small-scale experiments have found that the addition amount needs to be ≥4wt%. If the addition amount is too low, the yield rate of the final high-insulation and high-heat-insulation composite sheet is low and cannot meet the requirements of industrial-grade production. If the addition amount is too high, the mechanical properties and thermal conductivity of the final high-insulation and high-heat-insulation composite sheet will be affected. Small-scale experiments have found that the addition amount needs to be ≤8wt%.

[0118] Combining Examples 1, 17-25 and Comparative Examples 16-23 and Table 1, it can be seen that the mechanical properties and electrical strength of the high-insulation and high-heat-insulation composite sheets prepared by ultrafine mica powders obtained by different preparation processes are different, and from the yield rate of the small test results, the ultrafine mica powders obtained by different preparation processes affect the yield rate of the prepared high-insulation and high-heat-insulation composite sheets. When the particle size of the ultrafine mica powder is greater than 2000 mesh, the yield rate of the prepared high-insulation and high-heat-insulation composite sheets is low and cannot meet the needs of industrial production. The particle size of the ultrafine mica powder is between 2000-10000 mesh, and the particle size of 5000 mesh is relatively good.

[0119] Combining Examples 1, 17-25 and Comparative Examples 16-23 with Table 1, it can be seen that the use of the ultrafine mica powder prepared in this application can improve the overall physical and chemical properties, thermal insulation and noise reduction performance, processing performance and overall yield rate. Taking into account the production cost and comprehensive product performance, the preferred preparation scheme of the ultrafine mica powder is Preparation Example 12.

[0120] To sum up, the high-insulation and high-thermal insulation composite sheet in the present application has good flame retardant insulation and heat insulation effects. It is used between lithium battery cells to form a power battery module, which can improve the thermal runaway protection performance of the power battery module, and thus improve the driving safety performance of new energy vehicles. It also has the advantage of being lightweight and can improve the range of new energy vehicles.

[0121] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A high insulation and high heat insulation composite sheet used between lithium battery cells, characterized in that: The high-insulation and high-heat-insulation composite sheet has a through hole (10) formed inside thereof for achieving heat insulation and noise reduction; the through hole (10) is filled with aerogel (2); the high-insulation and high-heat-insulation composite sheet comprises a bottom plate (11), a cover plate (12), and a partition plate (13) fixedly connected between the bottom plate (11) and the cover plate (12); the thickness of the bottom plate (11) and the cover plate (12) are both 0.25-0.40 mm; the spacing between the bottom plate (11) and the cover plate (12) is 0. .60-0.80mm; the thickness of the partition plate (13) is 0.10-0.25mm; the high-insulation and high-heat-insulation composite sheet is made of high-insulation and high-heat-insulation composite masterbatch; the high-insulation and high-heat-insulation composite masterbatch is made of the following materials in mass percentage: 1-3wt% aramid nanofiber, 5-10wt% ultrafine mica powder, 2-5wt% nano silicon dioxide, 10-25% hollow glass microspheres, 4-8wt% plasticizer, and the balance is high temperature resistant resin.

2. The high insulation and high heat insulation composite sheet for lithium battery cells according to claim 1, characterized in that: The high temperature resistant resin is PI resin or PPS resin; the particle size of the ultrafine mica powder is ≤6.5 μm; the particle size of the hollow glass microspheres is ≤8.0 μm; and the particle size of the nano silicon dioxide is 50-200 nm.

3. The high insulation and high heat insulation composite sheet for lithium battery cells according to claim 1, characterized in that: The thickness of the bottom plate (11) and the cover plate (12) are both 0.25-0.30 mm; the spacing between the bottom plate (11) and the cover plate (12) is 0.75-0.80 mm; the spacing between adjacent partition plates (13) is 0.60-1.2 mm; the thickness of the partition plates (13) is 0.15-0.20 mm; the partition plates (13) are I-shaped, one end of which is fixedly connected to the cover plate (12) and the other end of which is integrally formed with the bottom plate (11); the ultrafine mica powder is a 5000 mesh sieve discharge material; and the hollow glass microspheres are a 5000 mesh sieve discharge material.

4. The high insulation and high heat insulation composite sheet for lithium battery cells according to claim 3, characterized in that: The high-insulation and high-heat-insulation composite masterbatch is made of 2.4-2.6wt% of aramid nanofibers, 7.5-8.5wt% of ultrafine mica powder, 2.5-3.0wt% of nano-silicon dioxide, 16-20% of hollow glass microspheres, 4-5wt% of hyperbranched PPS resin, and the remainder is injection-molding grade PPS resin; the high-insulation and high-heat-insulation composite masterbatch is made into a semi-finished high-insulation and high-heat-insulation composite sheet, and the semi-finished high-insulation and high-heat-insulation composite sheet comprises a bottom plate (11) and a partition plate (13).

5. The high insulation and high heat insulation composite sheet for lithium battery cells according to claim 4, characterized in that: The cover plate (12) is made of the following materials in percentage by weight: 1-3 wt% of aramid nanofibers, 2-5 wt% of nano silicon dioxide, 2-5 wt% of nano aluminum hydroxide, 10-25% of hollow glass microspheres, 4-8 wt% of a plasticizer, and the remainder being PI resin.

6. The high insulation and high heat insulation composite sheet for lithium battery cells according to claim 4, characterized in that: The preparation method of the superfine mica powder is as follows: S1, the mica powder is successively crushed by roller pressing, ball milling, and sieved through a sieve to obtain ultra-fine mica powder ≥ 2000 mesh; S2, 8-12 parts of superfine mica powder sieved through a mesh of ≥2000 and 1 part of bamboo-shaped boron nitride nanotubes are uniformly mixed to obtain a mixture, the mixture is mixed with anhydrous ethanol at a ratio of 1:(0.42-0.48), a ball-to-material ratio of 8-12, wet-milled at 1600-1800 rpm for 2-4 h, and dried to obtain modified BN@superfine mica powder; S3, taking 3-6 parts of the obtained modified BN@ultrafine mica powder and 100 parts of a 0.5-5wt% aqueous solution of methacryloxysilane for ultrasonic dispersion treatment for 0.5-2h, the ultrasonic frequency is 40-60kHz, the ultrasonic power is 600-1200W, and the surface modified BN@ultrafine mica powder is obtained by leaching and drying.

7. The high insulation and high heat insulation composite sheet for lithium battery cells according to claim 6, characterized in that: In the step S2, 9 parts of 5000 mesh sieved ultrafine mica powder and 1 part of bamboo-shaped boron nitride nanotubes are uniformly mixed to obtain a mixture, the mixture is mixed with anhydrous ethanol at a ratio of 1:0.45, with a ball-to-material ratio of 10, and wet-milled at 1800 rpm for 4 hours, and then dried to obtain modified BN@ultrafine mica powder.

8. A process for preparing a high insulation and high heat insulation composite sheet for lithium battery cells according to any one of claims 1 to 7, characterized in that: The following steps are involved: Step 1: 10-20 parts of aramid nanofibers, 78-88 parts of high temperature resistant resin, and 1-2 parts of coupling agent are mixed evenly and then put into a twin-screw extruder for melt extrusion, wire drawing, water cooling, granulation, and drying to obtain aramid nanofiber masterbatch; Step 2: Put aramid nanofiber masterbatch, ultrafine mica powder, nano silicon dioxide, hollow glass microspheres, plasticizer, and high temperature resistant resin into a twin-screw extruder for melt extrusion, wire drawing, water cooling, granulation, and drying to obtain high insulation and high thermal insulation composite masterbatch; the content of aramid nanofiber in the high insulation and high thermal insulation composite masterbatch is 1-3wt%; Step three, placing the high-insulation and high-heat-insulation composite masterbatch into a twin-screw extruder for melt extrusion and injection molding to obtain a semi-finished high-insulation and high-heat-insulation composite sheet, wherein the semi-finished high-insulation and high-heat-insulation composite sheet is composed of a bottom plate (11) and a partition plate (13), and one end of the partition plate (13) is integrally formed on the upper surface of the bottom plate (11); At the same time, the high-insulation and high-heat-insulation composite masterbatch is put into a twin-screw extruder for melt extrusion and injection molding to obtain a cover plate (12); Step 4: After the aerogel (2) is filled into the through hole (10) of the semi-finished high-insulation and high-heat-insulation composite sheet, the cover plate (12) is fixedly connected to one end of the partition plate (13) facing away from the upper surface of the bottom plate (11), thereby obtaining a finished high-insulation and high-heat-insulation composite sheet.

9. The process for preparing a high insulation and high heat insulation composite sheet for lithium battery cells according to claim 8, characterized in that: In the fourth step, the semi-finished high-insulation high-heat-insulation composite sheet is first subjected to low-temperature plasma treatment: ozone low-temperature plasma treatment is performed at 0-4°C for 240-320s, and after the plasma treatment is completed, the semi-finished high-insulation high-heat-insulation composite sheet is sealed at both ends using a mold, and an aerogel precursor liquid is injected into the through hole (10) of the semi-finished high-insulation high-heat-insulation composite sheet, and a hydrolysis and polycondensation reaction is performed at 120±5°C for 20-40h, and then cooled to room temperature, washed with water, and dried to fill the through hole (10) of the semi-finished high-insulation high-heat-insulation composite sheet with aerogel (2).

10. The process for preparing a high insulation and high heat insulation composite sheet for lithium battery cells according to claim 9, characterized in that: The aerogel (2) is a flexible aerogel, and the density of the flexible aerogel is 5-200 mg / cm 3 .

Citation Information

Cited By

  • Synergistic reinforced PC / ABS high-flame-retardant material and preparation method thereof

    CN121362447A

  • A fire-retardant thermal barrier composite material and a method of making the same

    CN122705150A